Esophageal perforation during intragastric balloon therapy: management of a patient with late referral - ERMERAK, NEZİH ONUR; UPRAK, TEVFİK KIVILCIM; LAÇİN, TUNÇ; YILDIZELİ, BEDRETTİN; YEGEN, ŞEVKET CUMHUR (My University, 2023)
Minimally invasive treatment modalities like intragastric balloon therapy (IBT) gained popularity in the treatment of obesity [1]. Some morbidities have been reported in the literature, but it is limited. Esophageal perforation is the most feared complication of the procedure. Although endoscopic stent placement can be chosen as a treatment option in stable patients, most of the patients are treated with surgical drainage and primary repair [2]. We report an unusual case of intragastric balloon placement complicated with esophageal perforation which was successfully treated with a surgical approach after late referral.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Cerrahi Tıp Bilimleri; Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Surgery Medicine Sciences; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Tarım Bilimleri; Klinik Tıp; BESLENME VE DİYETETİK; CERRAHİ; ENDOKRİNOLOJİ VE METABOLİZMA; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); AGRICULTURAL SCIENCES; CLINICAL MEDICINE; NUTRITION & DIETETICS; SURGERY; ENDOCRINOLOGY & METABOLISM; Cerrahi; Endokrinoloji, Diyabet ve Metabolizma; Beslenme ve Diyetetik; Surgery; Endocrinology, Diabetes and Metabolism